Corporate social responsibility legal analysis and social transformation: the South African experience in a comparative perspective - Mathibela, Kgwiti Prince (Department of Commercial Law, 2018)
This dissertation presents a legal and regulatory framework of corporate social responsibility (CSR) and the effect it has on social transformation in South Africa. It is premised on Dodds' theory of stakeholder protection which is articulated with greater clarity by Jeff Smith. He states that directors are agents of all stakeholders. In other words, they have the responsibility to ensure that every stakeholder's rights and interests are protected and fulfilled. This, he further explains, should be carried out by means of a balancing exercise between each stakeholder interest in every transaction. The dissertation demonstrates how the private sector can 'effectively' utilise principles of CRS to contribute towards and expedite social transformation. The significance of social transformation rests on it being a constitutional imperative as employed to redress the legacy of Apartheid. Lastly, the dissertation discusses CSR and how it affects social transformation in India and the United Kingdom (UK) with the aim of gleaning comparative insights. The dissertation then makes recommendations that the South African CSR legislation should embody objectives of our broader national interests similar to the Indian approach. In addition, it argues for a fully defined set of directors' duties which promotes compliance with CSR goals similar to the UK approach.